Protective Effect of Thyroxine on Minocycline Induced Thyroid Gland Damage - Naheed Gohar; Aisha Qamar; Asma Siddiqui; Tahira Assad; Sahal Salman (ziauddin University, 2020)
ABSTRACT Background: Thyroxine has shown beneficial effects on intelligence, learning, and memory process in patients of congenital hypothyroidism. Minocycline has been used in clinical practice for various indications and reported to have anti-thyroid effects. This study was specifically designed to observe the role of thyroxine on minocycline induced damage to thyroid gland. Methods: This experimental study was undertaken at Anatomy department of BMSI, JPMC, Karachi, for eight weeks, from October to November 2019. Thirty adult (10-12 months) male guinea pigs, weighing from 450-650 gm were obtained and divided into 3 groups. Group A served as control, group B was given Minocycline 0.02mg/gram/day once daily and group C was administered Minocycline in similar amount as group B along with thyroxine 0.5µg/gram/day for the same duration. Dosing was continued for 8 weeks, at the completion of which all the animals were sacrificed. Thyroid gland was processed and tissue sections were stained with Haematoxylin and Eosin for morphology. Results: The absolute weight of thyroid gland was significantly increased (p<0.001) in minocycline treated group B animals compared to the control animals, whereas substantial decrease (p<0.01) in absolute weight of thyroid gland was witnessed in group C in comparison to group B animals. The follicular cells showed hypertrophy and shrinkage of colloid in the thyroid follicles. These changes were prevented when animals were co-administered with thyroxine and minocycline in Group C. Conclusion: Concomitant administration of thyroxine with the antimicrobial drug minocycline showed protective effects of thyroxine on Minocycline induced damage to thyroid gland of animals.